IMF Staff Papers, Volume 51, Special Issue, IMF Fourth Annual Research Conference - Mody, Ashoka (IMF Staff Papers; IMF Staff Papers ;, 2004)
This is the 2004 (Volume 51) Special Issue of IMF Staff Papers, which includes 6 selected papers (from more than 20) that were presented at the IMF's Fourth Annual Research Conference, November 6-7, 2003.